EFFECTIVENESS OF HEALTH EDUCATION PROGRAMME ABOUT KNOWLEDGE ON PREVENTION AND MANAGEMENT OF IRON DEFICIENCY ANAEMIA AMONG ADOLESCENT GIRLS IN A SELECTED COLLEGE AT COIMBATORE - C. Chitraa,; Dr. Abirami. M, (The Bioscan, 2025)
Background: Iron deficiency anemia (IDA) is a leading micronutrient deficiency globally, particularly prevalent among adolescent girls due to increased physiological demands and poor dietary practices. Educational interventions, especially multimedia-based programs, have shown promise in improving awareness and management of IDA. Aim:To evaluate the effectiveness of a Health Education Programme on knowledge regarding the prevention and management of iron deficiency anemia among adolescent girls in a selected college in Coimbatore. Methods: A pre-experimental one-group pre-test post-test design was employed among 90 adolescent girls aged 17–19 years, selected through simple random sampling. A structured questionnaire assessed knowledge before and after a Health education Programme conducted over five days. Data were analyzed using descriptive statistics, paired t-test, and chi-square test, with significance set at p < 0.05. Results: Post-intervention findings revealed that 66.6% of participants demonstrated good knowledge, compared to lower levels prior to the intervention. The mean knowledge score improved from 2.5 (pre-test) to 3.5 (post-test), with a statistically significant paired t-value of 9.434 (p < 0.001), confirming the effectiveness of the educational program. Conclusion: The study highlights the positive impact of structured Health Education Programmes in enhancing knowledge related to IDA among adolescent girls. Integration of such interventions into school health systems may serve as an effective strategy to combat IDA at the community level.